Metodologia para análise de trincas de hidrogênio em soldas através de ensaios destrutivos e emissão acústica - Silva, Hebert Roberto da (2010)
The evolution of the processes of welding, registered in recent years in everybody, has occurred had to this process of manufacture to be related with the majority of the industrial applications, either in the construction as in the recovery of components. To this used procedures to evaluate the cracking sensibility in metallic structures comes being constantly perfected. With this, the scientific and technological improvement in these pursuings not only became a necessity, but a question of survival. Hydrogen induced cracking is one of the most serious and persistent defects found in the steels welding, as demonstrated by evolutions of costs and loss of time with repairs in welded parts. During welding, the heataffected zone (HAZ) is subjected to thermal cycles, which produces a change in both its microstructure and mechanical properties. In this sense, the objective was to present a methodology for determining and evaluating the training and crack propagation of hydrogen induced cracking using a system of Acoustic Emission for the test of susceptibility to crack (G-BOP and Tekken) in a High Strength Steel and Low Alloy. We tested specimens of the processes shielded metal arc welding (SMAW) and gas shielded metal arc welding (GMAW) in a comparative analysis with applications under favorable conditions the appearance of cracks as well as adopting best practices for its prevention. In the G-BOP tests and Tekken was noted a direct relationship between the occurrence of cracks in the specimen and the signal characteristic presented by the acoustic emission sensor. Thus, the testing methodology with the acoustic emission system used in this study proved to be efficient for your purpose.